Catalytic CH Bond Addition of Pyridines to Allenes by a Rare-Earth Catalyst - Song, Guoyong; Wang, Baoli; Nishiura, Masayoshi; Hou, Zhaomin (Chemistry : a European journal, 2015)
The catalytic CH addition of pyridines to allenes has been achieved for the first time by using a half‐sandwich scandium catalyst, thus constituting a straightforward and atom‐economical route for the synthesis of alkenylated pyridine derivatives. The reaction proceeded regio‐ and stereoselectively, affording a new family of alkenylated pyridine compounds which are otherwise difficult to synthesize. A cationic Sc‐η2‐pyridyl species was isolated and confirmed to be a key catalyst species in this transformation. Keep it allene: Half‐sandwich scandium dialkyls combined with a borate compound act as an efficient catalyst for the CH bond addition of pyridines to various terminal allenes, leading to formation of a new family of alkenylated pyridine derivatives in high yields and excellent regio‐ and stereoselectivity. A cationic scandium pyridyl species (see scheme) was isolated and confirmed to be a key active catalyst species.